Game Theory: Case Study of Gojek and Grab - Farhat Hafizh,; Anggi Ayu Sulistyani,; Ika Puspa Wardani,; Firli Indira Lestianika, (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
Online transportation in Indonesia has experienced rapid development in line with the competition between two industry giants, Gojek and Grab. These two companies are in fierce competition to offer technology-based transportation services and digital innovations. Gojek and Grab use various strategies, including pricing and promotions, to attract customers and expand their market. Game theory is used to analyze the optimal strategies implemented by both companies in facing each other, focusing on aspects of pricing, technological innovation, and consumer behavior. The analysis results show that Gojek tends to focus on safety and efficiency, while Grab is more aggressive in promotions and customer convenience. This competition has had a significant impact on the dynamics of the online transportation market in Indonesia and has triggered government regulations to maintain healthy competition and avoid monopolies. This research provides a comprehensive view of how the competitive strategies of both companies affect the online transportation industry as a whole.